In-situ Raman spectroscopic insight into charge delocalization-improved electrical conductivity in metal–cyanide frameworks. Issue 48 (1st December 2022) - Lu, Zhixuan; Huang, Yajun; Shao, Liting; Cao, Maofeng; Hu, Shu; Liu, Chuan; Wang, Xiang; Ren, Bin
Abstract : Raman spectroscopy reveals that the enhancement mechanism of electrical conductivity in Prussian Blue induced by K ions is charge delocalization. Abstract : Porous crystalline materials (PCMs) have attracted widespread attention due to their high porosity and chemical tunability. To solve the problem of the low electrical conductivity of traditional PCMs, a guest-promoted approach has been developed to impart electrical conductivity, whereas microscopic understanding of this process from experiments is largely lacking. Here we use in-situ electrochemical surface-enhanced Raman spectroscopy (EC-SERS) to investigate the microscopic mechanism of the enhanced electrical conductivity in metal–cyanide frameworks, in Prussian Blue (PB), induced by alkali metal ions. The EC-SERS result demonstrates that the charge is localized around the iron atom in PB and becomes delocalized on the CN bond after insertion of the alkali metal ions, verified by density functional theory (DFT) calculations. The enhanced electrical conductivity of PCMs promoted by the guest via the through-bond mechanism instead of the through-space hopping mechanism in pristine PB, offers a new approach to develop conductive PCMs.